TMOD-28. INTERLEUKIN-13 TARGETED PSEUDOMONAS TOXIN TREATMENT OF MALIGNANT PERIPHERAL NERVE SHEATH TUMORS - Mrowczynski, Oliver (Neuro Oncol, 2017)
Malignant peripheral nerve sheath tumors (MPNSTs) are soft tissue sarcomas that arise from peripheral nerves. A target of MPNSTs is the receptor for interleukin-13 (IL-13R). IL-13R has an α1 and α2 subtype, and activation of α1 leads to caspase-3 mediated apoptosis. MPNSTs have increased expression of the α2 subtype, IL-13Rα2. IL-13Rα2 is an oncogene that acts as a decoy receptor which has a higher affinity for IL-13, allowing cancer to evade death by binding and sequestering all of the IL-13 thus inhibiting α1 activation. Decreased α1 activation enhances tumor cell survival and augments the high potential for metastasis. The subsequent increased tumorigenicity is then followed by the devastating prognosis with five year survival ranging from a dismal 15-60%. MPNSTs are currently treated with surgical resection, sometimes requiring complete limb amputation, as well as chemoradiation, all of which demonstrate limited effectiveness, and highlight the necessity for novel therapies. The goal of this study was to demonstrate the effectiveness of intratumoral Interleukin-13 targeted pseudomonas exotoxin (IL13E13K-PE4E) for MPNST treatment. The upregulated IL-13Rα2 on MPNSTs provides a unique opportunity for utilizing IL13E13K-PE4E to precisely target MPNSTs and cause tumor cell death. We demonstrate that IL13E13K-PE4E treatment led to a 4-fold decrease in tumor progression in vivo. IHC analysis showed increased necrosis, decreased Ki67, and increased cleaved caspase-3, corroborating the in vivo findings. The specific targeting of IL-13Rα2 also leads to a decreased side effect profile due to minimal IL-13Rα2 expression in normal tissues. The current MPNST treatment paradigm is composed of 3-prongs: surgery, chemotherapy, and radiation, all of which have been demonstrated to be unsatisfactory. This study lays the groundwork for the change of this paradigm and subsequently optimal patient outcomes by the addition of a 4(th) prong, intratumoral treatment with IL13E13K-PE4E.